ToxNav germline genetic testing and PROMinet digital mobile application toxicity monitoring: Results of a prospective single‐center clinical utility study—PRECISE study. (4th September 2019) - Lee, Lennard Y. W.; Starkey, Thomas; Sivakumar, Shivan; Fotheringham, Susan; Mozolowski, Guy; Shearwood, Vanessa; Palles, Claire; Camilleri, Philip; Church, David; Kerr, Rachel; Kerr, David
Abstract: Introduction: In this study (PRECISE), we assess the clinical utility of a germline DNA sequencing‐based test (ToxNav) for mutations in DPYD and ENOSF1 genes to alter clinician‐prescribed fluoropyrimidine doses and the use of a digital application (PROMinet) to record patient‐reported chemotherapy toxicity. Materials and methods: Adult patients with a histological diagnosis of colorectal cancer (CRC) who consented to fluoropyrimidine‐based chemotherapy were recruited prospectively and given a digital application to monitor and record associated toxicities. Patient samples were analyzed for 18 germline coding variants in DPYD and 1 ENOSF1 variant. Results: Genetic testing was performed for 60 patients and identified one patient at increased risk of fluoropyrimidine‐based toxicities. Uptake of genetic testing was high and results were available on average 17 days from initial clinical encounter. Patient‐reported chemotherapy toxicity identified differences in 5‐fluorouracil vs capecitabine regime profiles and identified profiles associated with subsequent need for chemotherapy dose reduction and hospital admission. Discussion: The PRECISE clinical trial demonstrated that a germline DNA sequencing‐based test can provide clinically relevant information to alter clinicians' fluoropyrimidine prescription. The study also obtained high volume, high granularity patient‐reported toxicity data that might allow the improvement and personalization of chemotherapy management. Abstract : In the PRECISE study, we assess the clinical utility of a germline DNA sequencing‐based test to alter clinician‐prescribed fluoropyrimidine doses and the use of a digital application to record patient‐reported chemotherapy toxicity. Genetic testing identified one patient at increased risk of fluoropyrimidine‐based toxicities and patient‐reported toxicity identified differences in chemotherapy regime profiles and association with subsequent need for chemotherapy dose reduction and hospital admission. The study demonstrated the clinical utility of a germline DNA sequencing‐based test for providing information to alter clinicians' fluoropyrimidine prescription and obtained high volume, high granularity patient‐reported toxicity data.